An Underdiagnosed Hypothyroidism and Its Clinical Significance in Patients with Advanced Hepatocellular Carcinoma - Shao, Yu‐Yun (Oncologist, 2021)
BACKGROUND: Many systemic therapies for advanced hepatocellular carcinoma (HCC) may cause hypothyroidism; however, in these patients, hypothyroidism prevalence before therapy and its prognostic impact remain unclear. MATERIALS AND METHODS: We previously established a prospective cohort of patients who received sorafenib as first‐line therapy for advanced HCC. No patients had been clinically diagnosed with hypothyroidism before or during sorafenib treatment. We retrospectively determined the levels of thyrotropin and free thyroxine before initiation of systemic therapy. Hypothyroidism was defined as thyrotropin level higher than the upper limit of the normal range. Among patients with hypothyroidism, free thyroxine level less than the lower normal range was defined as overt hypothyroidism, and free thyroxine level within the normal range was defined as subclinical hypothyroidism. RESULTS: In total, 79 patients were enrolled; of them, 16 (20%) had hypothyroidism (overt hypothyroidism, 10; subclinical hypothyroidism, 6). Patients with hypothyroidism, compared with those without hypothyroidism, were more likely to be older than 65 years (56% vs. 29%, p = .037), have a serum α‐fetoprotein level of >400 ng/mL (81% vs. 52%, p = .037), and have a significantly poorer overall survival (OS; median, 5.5 vs. 11.6 months, p = .043). After adjusting for other potential prognostic factors, hypothyroidism remained an independent predictor for poorer OS (hazard ratio, 2.53, p = .018). Patients with overt hypothyroidism and subclinical hypothyroidism exhibited similarly poor OS (p = .768). CONCLUSION: Underdiagnosis of hypothyroidism in patients with advanced HCC was common. Hypothyroidism, whether overt or subclinical, is associated with poor prognosis of advanced HCC. IMPLICATIONS FOR PRACTICE: The results of this study showed the underdiagnosis of hypothyroidism in patients with advanced hepatocellular carcinoma (HCC) and its influence on prognosis. These findings implied the importance of thyroid function check before initiation of systemic therapy for patients with advanced HCC.